Curing the Sickie: Absence Management in NHS Scotland - Bestel, Segolene (2010)
Sickness absence is NHS Scotland is a serious problem. The average absence rate has been on a downward trend since 2007 but the rate is still high, creating substantial costs both economically and in terms of service delivery and the health of NHS employees. The results of this study show that sickness absence in NHS Scotland is not a general problem but a problem specific to certain areas of the organisation, most notably Nursing and Midwifery, and is linked to certain variables such as pay, gender and contract type. Management interventions to reduce the levels of sickness absence are in line with best practice and are seeing results. However, this study contends that the interventions are too general in nature and are treating the symptoms of absence rather than the specific causes. The author commends the data collection methods of NHS Scotland but calls for further qualitative research to investigate the true causes of absence in the most affected areas of the organisation.